Cash Flow Analysis In The Budget As A Management Function In Planning And Control At The BMT As-Salam Cooperative Demak - Andi Kurniawati (Universitas Islam Lamongan, 2022)
The development of cooperative business lines in Indonesia demands that cooperative management be carried out more professionally. Therefore, in order for each cooperative to survive or even grow and develop, cooperatives must pay close attention to the financial management of cooperatives. Every cooperative in running its business definitely needs capital. Cash is the wealth of cooperatives which is one of the elements of working capital that is very important in financing cooperative operations. Cash occupies a central position in an effort to maintain the smooth operation of cooperatives, so that the management function in planning and controlling the cash budget is necessary to ensure the survival of cooperatives.This study aims to determine the process of preparing the cash budget, analyzing the factors that cause the difference between the budget and the realization of the cash budget as well as planning and controlling the cash budget at the BMT As-Salam Demak Cooperative with the cash budget observation period in 2019 and 2020. In this study In this case, the researcher uses qualitative data analysis methods where the analysis is carried out using data in the amount that is poured to explain an explanation of the numbers then explained again in the form of a description with standard language.The results of the study found that cash flow as a planning and control tool in the BMT As-Salam Demak Cooperative was running well, the main factor causing the difference or difference between the budget and the realization of cash flow was in the realization of the previous year's budget, the BMT As-Salam Demak Cooperative. using the Bottom Up approach, namely budget planning is carried out by all parties in the organization, it would be even better if using the Mixture approach because to overcome the weaknesses in the Bottom Up approach.The development of cooperative business lines in Indonesia demands that cooperative management be carried out more professionally. Therefore, in order for each cooperative to survive or even grow and develop, cooperatives must pay close attention to the financial management of cooperatives. Every cooperative in running its business definitely needs capital. Cash is the wealth of cooperatives which is one of the elements of working capital that is very important in financing cooperative operations. Cash occupies a central position in an effort to maintain the smooth operation of cooperatives, so that the management function in planning and controlling the cash budget is necessary to ensure the survival of cooperatives.This study aims to determine the process of preparing the cash budget, analyzing the factors that cause the difference between the budget and the realization of the cash budget as well as planning and controlling the cash budget at the BMT As-Salam Demak Cooperative with the cash budget observation period in 2019 and 2020. In this study In this case, the researcher uses qualitative data analysis methods where the analysis is carried out using data in the amount that is poured to explain an explanation of the numbers then explained again in the form of a description with standard language.The results of the study found that cash flow as a planning and control tool in the BMT As-Salam Demak Cooperative was running well, the main factor causing the difference or difference between the budget and the realization of cash flow was in the realization of the previous year's budget, the BMT As-Salam Demak Cooperative. using the Bottom Up approach, namely budget planning is carried out by all parties in the organization, it would be even better if using the Mixture approach because to overcome the weaknesses in the Bottom Up approach.